1986
DOI: 10.1210/jcem-63-6-1257
|View full text |Cite
|
Sign up to set email alerts
|

Sex Steroid, Gonadotropin, Cortisol, and Prolactin Levels in Healthy, Massively Obese Women: Correlation with Abdominal Fat Cell Size and Effect of Weight Reduction*

Abstract: To examine hormonal status in obese, gynecologically normal women we studied 25 regularly menstruating, massively obese (mean weight, 120 kg) women participating in a weight reduction program and 25 age-matched normal weight (mean weight, 60 kg) women. Serum 17 beta-estradiol (E2), estrone (E1), androstenedione (A), dehydroepiandrosterone sulfate, testosterone, LH, FSH, PRL, and cortisol concentrations were measured during the follicular phase of the menstrual cycle. Waist to hip ratio and abdominal fat cell s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
50
0
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(62 citation statements)
references
References 24 publications
11
50
0
1
Order By: Relevance
“…The inverse association between follicularphase E 2 and BMI is similar to previous reports from studies performed in massively obese women (Grenman et al, 1986), despite the fact that women in our study were within a normal range of BMI (18-31 kg/m 2 ). Also consistent with previous reports (Key et al, 2001), we found an inverse correlation between SHBG and BMI.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The inverse association between follicularphase E 2 and BMI is similar to previous reports from studies performed in massively obese women (Grenman et al, 1986), despite the fact that women in our study were within a normal range of BMI (18-31 kg/m 2 ). Also consistent with previous reports (Key et al, 2001), we found an inverse correlation between SHBG and BMI.…”
Section: Discussionsupporting
confidence: 92%
“…The inverse relationship found between SHBG and BMI is likely explained by the effect of BMI increasing insulin levels with subsequent inhibition of liver production of SHBG (Plymate et al, 1988;Franks et al, 1991). Although the inverse relationship between A and BMI in our cohort was only of borderline significance, it is consistent with other reports (Grenman et al, 1986), and may be explained by the increased metabolic clearance rate in obesity (Kirschner et al, 1983).…”
Section: Discussionsupporting
confidence: 89%
“…1,3,6,16 Obesity, especially android type obesity, is commonly associated with the insulin resistant state and secondary hyperinsulinaemia. 1,3,6,12,18,20,34,35 We also found signi®cantly higher insulin levels in women with android obesity. The insulin resistance was greater with increasing WHR.…”
Section: Discussionsupporting
confidence: 62%
“…23,24,34±36,39±41 Especially women with android obesity seem to be prone to develop menstrual disorders. 12,15,18,20,22,34 Even in lean women, an increasing WHR was associated with a reduced chance of conception. 24 The possible role of insulin as the mediating factor has aroused a great deal of interest in recent years.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation